Preparation method and application of copper nanoclusters with peroxidase catalytic activity
By using penicillamine as a reducing agent and stabilizing ligand, copper nanoclusters were synthesized by one-pot method, which solved the problems of easy oxidation and poor stability of copper nanoclusters, and achieved the preparation and application of high-quality and low-toxic copper nanoclusters.
Patent Information
- Application Number
- CN202410647850.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-23
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-05-23
AI Technical Summary
Copper nanoclusters are limited in their research and application due to their oxidation, poor stability, difficult preparation and high toxicity.
Penicillamine was used as a reducing agent and stabilized ligand to synthesize copper nanoclusters with fluorescent and peroxidase activity by a one-pot method. The method includes adding penicillamine and copper nitrate solutions to the acetic acid-acetate buffer solution, followed by heating and reaction, and finally purifying the copper nanoclusters by centrifugation and water washing.
The obtained copper nanoclusters have high stability, low toxicity and strong catalytic activity, and are suitable for biological analysis and detection fields.
Smart Images

Figure CN118594538B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of composite nano materials, and specifically discloses a preparation method and application of copper nano clusters with peroxidase catalytic activity. Technical Background
[0002] Among various natural enzymes, peroxidase (POD) is a widely existing oxidoreductase that catalyzes the 2 O 2 ) oxidizes some reducing substrates. For this reaction, hydrogen peroxide is an intermediate product of many reactions and plays an important role in the fields of food, environment and pharmaceuticals. On the other hand, when hydrogen peroxide decomposes, it can produce hydroxyl radicals, which have a wide range of applications in the biomedical field. However, the high production cost and low stability of natural enzymes limit their application range.
[0003] In recent years, with the development of various nanocomposites, scientists have discovered that by combining biology with nanotechnology, an artificial enzyme that has both nanomaterial and enzyme-mimicking properties can be prepared, namely "nanozymes". Nanozymes are a general term for nanomaterials with catalytic activity similar to that of natural enzymes. Compared with natural enzymes, nanozymes have the advantages of low cost, high stability, long service life, and easy storage. Therefore, the ability to simulate POD catalytic activity is widely used in biological analysis and detection, biological imaging, antibacterial and anti-tumor treatment, showing great development potential in the field of biological analysis.
[0004] Precious metal nanoclusters are a new type of nanomaterial in recent years. Currently, palladium, platinum, gold, silver, copper, etc. are used as precious metal atomic centers to prepare nanoclusters. Compared with other metals, copper has a wider source, is cheap and easy to obtain, and is widely involved in biochemical reactions in the body, with better biocompatibility. At the same time, copper is an essential micronutrient for the human body and a component of many important enzymes. Based on Cu + The nano-Fenton reagent has a stronger pH adaptability and still has high catalytic activity in slightly acidic and neutral media. 2+ / Cu + The redox potential (0.16 V) is significantly lower than that of Fe 3+ / Fe 2+ (0.77V), the highest reaction rate can reach Fe 2+Therefore, copper nanoclusters have considerable potential as peroxidase mimics in catalytic applications, such as catalytic reduction, catalytic oxidation, and catalytic cycloaddition reactions. In addition to these industrial catalytic reactions, CuNCs also perform well in the field of bio-related catalysis, and can mimic three major peroxidases, namely catalase, peroxidase, and superoxide dismutase, thereby regulating the level of intracellular reactive oxygen species and changing the ability to oxidative stress to treat related diseases. Typically, CuNCs can catalyze H 2 O 2 Decompose into O 2- and ·OH, and further oxidizes the substrate (such as 3,3',5,5'tetramethylbenzidine (TMB)), so that the system changes from colorless to blue formed by the oxidation of the substrate. Therefore, it can be combined with the substrate TMB to construct a colorimetric biomolecule detection system, and a visual qualitative and quantitative analysis of cholesterol and glucose was performed.
[0005] However, at present, the research on copper nanoclusters is limited due to problems such as easy oxidation, poor stability, difficulty in preparation, and high toxicity. Therefore, in view of the problems existing in CuNCs, exploring the synthesis method of CuNCs that is easy to prepare, stable, low in toxicity, and high in quality will lay a solid foundation for its research in various directions. Summary of the invention
[0006] In view of the above problems, the present invention discloses a preparation method and application of copper nanoclusters with peroxidase catalytic activity.
[0007] The present invention includes the following technical solutions:
[0008] A method for preparing copper nanoclusters with peroxidase catalytic activity comprises at least the following steps: adding penicillamine (D-Penicillamine, DPA) into an acetic acid-acetate buffer solution to fully dissolve it, then adding a copper nitrate solution, heating to 25-60°C when white turbidity is generated, and heating the reaction for 20-60 minutes; after the reaction is completed, centrifuging the precipitate to obtain the copper nanoclusters DPA-CuNCs with peroxidase catalytic activity by purification.
[0009] Furthermore, in the above method for preparing copper nanoclusters with peroxidase catalytic activity, the molar ratio of penicillamine to copper nitrate is 8-16:1-4.
[0010] Furthermore, in the above-mentioned method for preparing copper nanoclusters with peroxidase catalytic activity, the molar ratio of penicillamine to copper nitrate is 8:1 or 5:1; in our embodiments, we found the following facts: when the molar ratio of penicillamine to copper nitrate is 8:1, the fluorescence intensity of the prepared copper nanoclusters reaches the maximum; when the molar ratio of penicillamine to copper nitrate is 5:1, the peroxidase activity of the prepared copper nanoclusters is the strongest.
[0011] Furthermore, in the above method for preparing copper nanoclusters with peroxidase catalytic activity, the pH value of the acetic acid-acetate buffer solution is 2-4, preferably, the pH value is 3.
[0012] Furthermore, the method for preparing the above-mentioned copper nanoclusters having peroxidase catalytic activity comprises the following steps:
[0013] 1) Weigh 0.2983-0.5966 g of penicillamine and add it into a 250 mL three-necked flask containing 50-100 mL of acetic acid-acetate buffer solution, pH 3, and fully dissolve it under magnetic stirring at 400-600 rpm, then add 2.5-5.0 mL of 0.1-0.2 mol / L copper nitrate solution, and the solution quickly turns into a yellow transparent solution;
[0014] 2) Continue stirring until a small amount of white turbidity appears in the solution, then slowly heat the solution to 25-60°C and react for 20-60 minutes to terminate the reaction;
[0015] 3) After the product is cooled, a light yellow emulsion is obtained, and the light yellow precipitate is separated by centrifugation at a speed of 5000-10000 rpm for 5-10 min, and then washed with ultrapure water 2-3 times. The precipitate in the centrifuge tube is collected and freeze-dried in a freeze dryer. The freeze-dried powder sample is stored in a refrigerator at 4°C for subsequent use.
[0016] Preferably, the method for preparing the above-mentioned copper nanoclusters having peroxidase catalytic activity comprises the following steps:
[0017] 1) At 25°C, weigh 0.5220 g of penicillamine and add it into a 250 mL three-necked flask filled with 100 mL of acetic acid-acetate buffer solution. Stir at 550 rpm to fully dissolve it. Add 5.0 mL of 0.1 mol / L copper nitrate solution, and the solution quickly turns into a yellow transparent solution.
[0018] 2) Continue stirring until a small amount of white turbidity is generated in the solution. Then slowly heat the solution to 50°C and react for 40 minutes before the reaction is terminated;
[0019] 3) After the product is cooled, a light yellow emulsion is obtained. The emulsion is centrifuged at 8000 rpm for 10 min, the supernatant is discarded, and the precipitate is washed with ultrapure water and centrifuged three times. The precipitate in the centrifuge tube is collected and freeze-dried in a freeze dryer. The freeze-dried powder sample is stored in a 4°C refrigerator for subsequent use.
[0020] The invention also discloses a copper nanocluster with peroxidase catalytic activity, which is prepared by the above method.
[0021] Furthermore, the copper nanoclusters having peroxidase catalytic activity have an average particle size of 2.5 to 5.5 nm.
[0022] The invention also discloses the use of the copper nanoclusters with peroxidase catalytic activity in visual qualitative or quantitative analysis of cholesterol or glucose.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] (1) The present invention uses penicillamine as a reducing agent and a stabilizing ligand to synthesize copper nanoclusters with fluorescence and peroxidase activity through a one-pot method. Penicillamine is a hydrolysis metabolite of penicillin, which has important applications in the treatment of autoimmune diseases and heavy metal poisoning and has good biocompatibility. The inherent metal chelating properties of penicillamine ensure the formation of high-affinity metal ligand clusters, and the carboxyl and amino groups in the molecule also provide a protective layer, so that DPA-CuNCs have the advantages of good dispersibility in water, high stability, low toxicity, etc., while ensuring the stability of the catalytic activity of CuNCs.
[0025] (2) The synthesis process of the present invention adopts a one-pot method and uses a simple reflux condenser, which is convenient to operate and has high synthesis efficiency. At the same time, a magnetic stirring device is used to reduce the sedimentation of the product in the system, so as to obtain copper nanoclusters with controllable morphology, uniform size and good dispersibility. The reaction medium is an acetate buffer solution with a pH of 3, and the copper nanoclusters obtained have good stability, low reaction temperature, and short reaction time. The reaction product is separated and purified by centrifugation and water washing, and the process is simple and green.
[0026] (3) The DPA-CuNCs synthesized by the present invention were characterized by dynamic light scattering, transmission electron microscopy, infrared and other analytical methods, the fluorescence properties were analyzed by fluorescence spectrophotometer, and the peroxidase activity was analyzed by UV-visible spectrophotometer. The effects of feed ratio, temperature, and synthesis time on the peroxidase activity of copper nanoclusters were systematically studied; the TMB colorimetric detection system based on DPA-CuNCs was designed using enzyme activity, and the qualitative and quantitative analysis of cholesterol and glucose was visualized. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 : IR spectra of DPA-CuNCs and DPA;
[0028] Figure 2 :Transmission electron microscopy images of DPA-CuNCs;
[0029] Figure 3 : Fluorescence spectrum of DPA-CuNCs;
[0030] Figure 4 :Effects of different reaction ratios on the peroxidase activity of DPA-CuNCs. (a) Different DPA / Cu(NO 3 ) 2 UV absorption spectra of the catalytic activity of DPA-CuNCs synthesized with different molar ratios; (b) 3 ) 2 The absorbance at the maximum absorption wavelength (652 nm) of DPA-CuNCs synthesized by molar ratio;
[0031] Figure 5 :Enzyme catalytic activity of DPA-CuNCs prepared at different reaction temperatures. (a) Ultraviolet absorption spectra of catalytic activity of DPA-CuNCs synthesized at different reaction temperatures; (b) Absorbance at the maximum absorption wavelength (652nm) of DPA-CuNCs synthesized at different reaction temperatures;
[0032] Figure 6 :The effect of different reaction times on the peroxidase activity of DPA-CuNCs. (a) UV absorption spectra of catalytic activity of DPA-CuNCs synthesized at different reaction times; (b) Absorbance at the maximum absorption wavelength (652 nm) of DPA-CuNCs synthesized at different reaction times;
[0033] Figure 7 :Effects of different pH buffers on the peroxidase activity of DPA-CuNCs. (a) UV absorption spectra of DPA-CuNCs catalytic activity under different pH conditions; (b) Absorbance at the maximum absorption wavelength (652 nm) of DPA-CuNCs catalytic activity under different pH conditions;
[0034] Figure 8 :Enzyme catalytic activity of DPA-CuNCs at different concentrations. Ultraviolet absorption spectra of catalytic activity of DPA-CuNCs at different concentrations; (b) Absorbance at the maximum absorption wavelength (652nm) of catalytic activity of DPA-CuNCs at different concentrations;
[0035] Fig. 9 :Different H 2 O 2(a) The absorbance at the maximum absorption wavelength (652 nm) of the catalytic activity of DPA-CuNCs under different concentrations of hydrogen peroxide; (b) The absorbance at the maximum absorption wavelength (652 nm) of the catalytic activity of DPA-CuNCs under different concentrations of hydrogen peroxide;
[0036] Fig.10 :UV absorption spectra of enzyme activity corresponding to different concentrations of TMB. UV absorption spectra of DPA-CuNCs catalytic activity under different concentrations of TMB; (b) Absorbance at the maximum absorption wavelength (652nm) of DPA-CuNCs catalytic activity under different concentrations of TMB;
[0037] Fig.11 :DPA-CuNCs based on H 2 O 2 The enzyme kinetics. TMB concentration was 1.0 mM, and the H 2 O 2 Concentration rate change curve; (d) Double reciprocal Lineweaver-Burk plot based on Michaelis-Menten equation;
[0038] Fig.12 :Stability of fluorescence and enzyme catalytic activity of DPA-CuNCs during 3 months of storage;
[0039] Fig.13 :DPA-CuNCs are applied to cholesterol detection. (a) UV absorption spectra under different cholesterol concentrations; (b) Linear relationship between cholesterol concentration and absorbance at the maximum wavelength (652nm);
[0040] Fig.14 :DPA-CuNCs are applied to glucose detection. (a) UV absorption spectra under different glucose concentrations; (b) Linear relationship between glucose concentration and absorbance at the maximum wavelength (652nm);
[0041] Fig.15 : Cytotoxicity of DPA-CuNCs towards LO2. DETAILED DESCRIPTION
[0042] The embodiments of the present invention include the following test methods (1) to (5).
[0043] (1) Preparation of DPA-CuNCs
[0044] Weigh 0.2983-0.5966g of penicillamine and add it to a 250mL three-necked flask containing 50-100mL acetic acid-acetate buffer solution. Dissolve it fully under magnetic stirring at 400-600rpm, then add 2.5-5.0mL of 0.1-0.2mol / L copper nitrate solution, and the solution quickly turns into a yellow transparent solution. Continue stirring. When a small amount of white turbidity is produced in the solution, slowly heat the solution to 25-60℃ and react for 20-60min to end the reaction. After the product is cooled, a light yellow emulsion is obtained. Centrifuge at 5000-10000rpm for 5-10min to separate the light yellow precipitate, and then wash it with ultrapure water 2-3 times. Collect the precipitate in the centrifuge tube and freeze-dry it in a freeze dryer. The freeze-dried powder sample is stored in a 4℃ refrigerator for subsequent use.
[0045] (2) Analysis of peroxidase catalytic activity of DPA-CuNCs
[0046] TMB (0.05-1 mM), H 2 O 2 (0.05~9mM) and DPA-CuNCs (0~30μg mL -1 ) were evenly mixed, incubated for 0 to 60 min, and then the maximum absorbance at 652 nm was measured on a UV-visible spectrophotometer.
[0047] (3) Stability analysis
[0048] In order to analyze the storage stability of freeze-dried DPA-CuNCs powder, the fluorescence intensity and peroxidase activity were measured in a refrigerator at 0-4°C for 0 to 3 months.
[0049] (4) Establishment of cholesterol concentration detection system
[0050] 200-300 μL cholesterol ethanol solution (0.05-2.0 mM) of different concentrations and 25-75 μL 1-5 mg / mL cholesterol oxidase (COD) solution were added to 1.5-2.0 mL pure water, mixed, and incubated at 37°C for 15-45 min; 1.5-2.0 mL 0.01-0.05 M HAc-NaAc buffer (pH 3.0-5.0), 200-300 μL 10-35 mM 3,3',5,5'-tetramethylbenzidine (TMB) ethanol solution and 25-75 μL 0.05-0.2 mg / mL copper nanocluster dispersion were added to the above mixed reaction, mixed, and incubated at room temperature for 5-30 min. Then, the UV-Visa method was used to measure the ultraviolet spectrum of the sample, and the change law of absorbance at the maximum absorption wavelength was observed to draw a standard curve of cholesterol concentration-absorbance.
[0051] (5) Establishment of glucose concentration detection system
[0052] 25-75 μL of 5 mg / mL glucose oxidase solution and 200-300 μL of 0.6-1.0 mM glucose solution were added to 1.5-2.0 mL of pure water, mixed, and incubated at 37°C for 15-45 min; (2) 1.5-2.0 mL of 0.01-0.05 M HAc-NaAc buffer solution pH (3.0-5.0), 200-300 μL of 10-35 mM 3,3',5,5'-tetramethylbenzidine ethanol solution, and 25-75 μL of 0.1-0.3 mg / mL penicillamine copper nanocluster dispersion were added to the above solution, mixed, and incubated at room temperature for 10-60 min. The absorbance at 652 nm was then measured by a UV spectrophotometer.
[0053] (6) Cytotoxicity analysis
[0054] The cytotoxicity was determined using the CCK-8 method. Normal human liver cells (LO2 cells) were used to evaluate the biocompatibility of DPA-CuNCs. The cell culture method and specific operation steps were as follows: the cells were digested, counted, and prepared to a concentration of 5×10 4 ~1×10 5 50-200 μL of cell suspension (5×10 cells / mL) was added to each well of a 96-well cell culture plate. 3 ~1×10 4 The cell culture plate was placed at 37°C and 5% CO 2 The cells were cultured in an incubator for 24 h. Complete culture medium (80% to 90% RPMI1640 culture medium + 10% to 20% fetal bovine serum) was used to prepare DPA-CuNCs working solutions with a concentration of 0 to 10 μg / mL. 50 to 200 μL of the corresponding working solution was added to each well, and 3 replicates were set for each concentration. The cells were incubated at 37°C and 5% CO 2 After culturing in the incubator for 24 hours, the supernatant was discarded; the 96-well plate was stained with CCK-8, and the OD value was measured at λ=450nm.
[0055] The exemplary embodiments of the present disclosure will be described in more detail below with reference to the accompanying drawings. Although the exemplary embodiments of the present disclosure are shown in the accompanying drawings, it should be understood that the present disclosure can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided in order to enable a more thorough understanding of the present disclosure and to fully convey the scope of the present disclosure to those skilled in the art.
[0056] Example 1
[0057] Best practice: Preparation and performance testing of DPA-CuNCs
[0058] (1) Preparation of DPA-CuNCs
[0059] At 25°C, weigh 0.5220g of penicillamine (D-PA) and add it to a 250mL three-necked flask containing 100mL of pH3 acetic acid-acetate buffer solution. Stir at 550rpm to fully dissolve it, add 5.0mL of 0.1mol / L copper nitrate solution, and the solution quickly turns into a yellow transparent solution. Continue stirring, and a small amount of white turbidity will be produced in the solution. At this time, slowly heat the solution to 50°C and react for 40min to end the reaction. After the product is cooled, a light yellow emulsion is obtained. The emulsion is centrifuged at 8000rpm for 10min, the supernatant is discarded, and the precipitate is washed with ultrapure water and centrifuged 3 times. Collect the precipitate in the centrifuge tube and freeze-dry it in a freeze dryer. The freeze-dried powder sample is stored in a 4°C refrigerator for subsequent use.
[0060] (2) Peroxidase catalytic activity of DPA-CuNCs
[0061] TMB (1 mM), H 2 O 2 (9 mM) and DPA-CuNCs (30 μg mL -1 ) were evenly mixed, incubated for 0 to 60 min, and then the maximum absorbance at 652 nm was measured on a UV-visible spectrophotometer.
[0062] (3) Stability analysis
[0063] In order to analyze the storage stability of freeze-dried DPA-CuNCs powder, the fluorescence intensity and enzyme catalytic activity were measured in a refrigerator at 0-4°C for 0 to 3 months.
[0064] (4) Establishment of cholesterol concentration detection system
[0065] 250 μL cholesterol ethanol solution of different concentrations (0.1-1.0 mM) and 50 μL 2 mg / mL cholesterol oxidase (COD) solution were added to 1.7 mL pure water, mixed, and incubated at 37 ° C for 30 min; 1.7 mL 0.02 M HAc-NaAc buffer (pH 3.0), 250 μL 32 mM 3,3',5,5'-tetramethylbenzidine (TMB) ethanol solution and 50 μL 0.1 mg / mL copper nanocluster dispersion were added to the above mixed reaction, mixed. Incubate at room temperature for 10 min. Then, the UV-Visa method was used to measure the ultraviolet spectrum of the sample, and the change law of absorbance at the maximum absorption wavelength was observed to draw a standard curve of cholesterol concentration-absorbance.
[0066] (5) Establishment of glucose concentration detection system
[0067] 50 μL of 5 mg / mL glucose oxidase solution and 250 μL of 0.6-1.0 mM glucose solution were added to 1.7 mL of pure water, mixed, and incubated at 37°C for 30 min; (2) 1.7 mL of 0.02 M HAc-NaAc buffer (pH 3.0), 250 μL of 32 mM 3,3',5,5'-tetramethylbenzidine ethanol solution, and 50 μL of 0.2 mg / mL penicillamine copper nanocluster dispersion were added to the above solution, mixed, and incubated at room temperature for 60 min. The absorbance at 652 nm was then measured by a UV spectrophotometer.
[0068] (6) Cytotoxicity analysis
[0069] The cytotoxicity was determined using the CCK-8 method. Normal human liver cells (LO2 cells) were used to evaluate the biocompatibility of DPA-CuNCs. The cell culture method and specific operation steps are as follows: the cells were digested, counted, and prepared to a concentration of 8×10 4 100 μL of cell suspension (8×10 cells / mL) was added to each well of a 96-well cell culture plate. 3 The cell culture plate was placed at 37°C and 5% CO 2 The cells were cultured in an incubator for 24 h. Complete culture medium (90% RPMI1640 culture medium + 10% fetal bovine serum) was used to prepare DPA-CuNCs working solutions with concentrations ranging from 0 to 10 μg / mL. 100 μL of the corresponding working solution was added to each well, and 3 replicates were set for each concentration. The cells were incubated at 37°C and 5% CO 2 After culturing in the incubator for 24 hours, the supernatant was discarded; the 96-well plate was stained with CCK-8, and the OD value was measured at λ=450nm.
[0070] Example 2
[0071] Analysis of the experimental results of Example 1.
[0072] (1) The surface functional groups of penicillamine (DPA) and copper nanoclusters (DPA-CuNCs) were measured and analyzed by Fourier transform infrared spectroscopy (FT-IR). Figure 1 For DPA-CuNCs, secondary ammonia (3401 cm -1 ) and carboxyl (1712cm -1 ) can protect CuNCs from aggregation and increase the stability of the clusters. -1The absorption peak at 2510 cm-1 is attributed to the stretching vibration peak of -SH, while the absorption peak at 2510 cm-1 does not exist in the infrared spectrum of DPA-CuNCs. -1 The absorption peak at , indicating that the -SH of DPA interacts with Cu atoms in DPA-CuNCs to form Cu-S bonds.
[0073] (2) The morphology of the prepared DPA-CuNCs was analyzed by TEM ( Figure 2 ), it can be seen that the prepared DPS-CuNCs have a particle size of 2.5-5.5 nm, appearing as round clusters as a whole, with relatively uniform particle size and good overall dispersion.
[0074] (3) Figure 3 It shows that the fluorescence intensity of copper nanoclusters (DPA-CuNCs) increases with the increase of DPA / Cu(NO 3 ) 2 The fluorescence intensity of copper nanoclusters increases with the increase of the molar ratio, and reaches the maximum when the molar ratio is 8:1.
[0075] (4) Figure 4 It was shown that the UV spectrophotometric method was used to detect H 2 O 2 +TMB+DPA-CuNCs catalytic system has a positive correlation with the catalytic activity of peroxidase at 652 nm. 3 ) 2 As the molar ratio increases, the peroxidase activity increases first and then decreases. It reaches the maximum value at a molar ratio of 5:1. If the molar ratio continues to increase, the peroxidase activity begins to gradually decrease. This may be because the feed ratio is too large, resulting in some unreacted penicillamine in the reaction system. Free penicillamine will reduce TMB oxide, resulting in an overall decrease in the peroxidase activity of DPA-CuNCs.
[0076] (5) Figure 5 It shows that the ultraviolet absorbance of CuNCs at 50℃ is much greater than that at other reaction temperatures. This is because the yield of CuNCs is low at lower reaction temperatures, while at higher temperatures, it is not conducive to the synthesis of small-sized copper nanoclusters. The prepared copper nanoclusters are uneven in size, resulting in reduced enzyme activity. Based on the experimental results, we determined 50℃ as the optimal temperature for the reaction.
[0077] (6) Explore the reaction time. Figure 6It shows that between 20-40 minutes, the intensity of ultraviolet absorbance gradually increases; between 40-60 minutes, the intensity of ultraviolet absorbance begins to decrease. When the reaction time is 40 minutes, the ultraviolet absorbance is the maximum; after the reaction time is extended, the ultraviolet absorbance decreases. Through experiments, it can be concluded that the optimal reaction time of CuNCs is 40 minutes.
[0078] (7) Figure 7 As shown, different buffer variables of different pH values were prepared (pH was 2.0, 3.0, 4.0, 5.0, 6.0, 7.0, 8.0). Through ultraviolet spectroscopy analysis, the results showed that the ultraviolet absorbance at 652nm was the largest at pH 2.0. However, at pH 2.0, the acidity was too strong. Therefore, the acetic acid-sodium acetate buffer solution of pH 3.0 was selected as the buffer solution for subsequent experiments.
[0079] (8) Figure 8 As shown, different concentrations of DPA-CuNCs variable groups (0, 5, 10, 20, 30 μg / mL, respectively) were prepared, and their absorbance at 652 nm increased with the increase of DPA-CuNCs concentration, and 30 μg / mL was selected as the DPA-CuNCs concentration for subsequent enzymatic kinetic experiments.
[0080] (9) By Fig. 9 It can be seen that within the concentration range of 0.05 to 9 mM, an absorption peak appears at 652 nm, and as H 2 O 2 As the concentration of increases, the absorbance increases, indicating that the peroxidase activity increases and has a good linear relationship. Therefore, H 2 O 2 The optimal concentration is 9 mM.
[0081] (10) Fig.10 As shown in the figure, in the catalytic system, with the increase of TMB concentration, the absorbance gradually increased, indicating that the more TMB content, the more TMB oxide was generated under the enzyme catalysis of DPA-CuNCs. When the TMB concentration increased from 0.05mM to 1.0mM, the ultraviolet absorbance at 652nm increased with the increase of TMB concentration during the same incubation time, and had a good linear relationship in the range of 0.05-1.0mM.
[0082] (11) The enzymatic kinetic results showed that DPA-CuNCs could effectively inhibit H 2 O 2 Enzyme kinetic analysis ( Fig.11 (a) and (b) follow the typical Michaelis-Menten model. Therefore, the Michaelis-Menten model was used to evaluate the H2 O 2 The catalytic activity of DPA-CuNCs on H 2 O 2 V max The value is 4.638×10 -8 M / s, apparent K m The value is 3.99 mM, which is consistent with the K value of natural enzyme HRP reported in the literature. m value (3.7mM) is comparable and much smaller than Fe 2 O 3 K m value (323.6 mM), indicating that DPA-CuNCs has a strong affinity for substrate H 2 O 2 With good affinity, DPA-CuNCs exhibited excellent peroxidase-like catalytic activity.
[0083] (12) Stability test results ( Fig.12 ) showed that, with the initial fluorescence intensity and enzyme catalytic activity as 100%, the fluorescence intensity and enzyme catalytic activity of DPA-CuNCs remained almost unchanged within 3 months of storage in a 0-4°C refrigerator. Even after 3 months, the fluorescence intensity and enzyme catalytic activity were still close to 90%.
[0084] (13) Fig.13 As shown in (a), the absorbance value at 652nm gradually increases with the increase of cholesterol concentration. Fig.13 As shown in (b), the cholesterol concentration showed a good linear relationship with the absorbance when it was 0.1-1.0 mM, and the related equation was A=0.3433C-0.0085, and the linear regression coefficient R 2 =0.9869, and the limit of detection (LOD) was 12.0 μM (limit of detection = 3σ / S, where σ is the standard deviation of the blank (σ = 0.001 mM), and S is the slope of the standard curve).
[0085] (14) Fig.14 As shown in (a), the absorbance value at 652nm gradually increases with the increase of glucose concentration. Fig.14 As shown in (b), the glucose concentration showed a good linear relationship with the absorbance when it was 0.6-1.0 mM, and the correlation equation was A=0.192C-0.040, and the linear regression coefficient R 2 =0.991, and the detection limit was 14.0 μM (detection limit = 3σ / S, where σ is the standard deviation of the blank (σ = 0.0009 mM), and S is the slope of the standard curve).
[0086] (15) Human normal hepatocytes (LO2) were co-incubated with DPA-CuNCs for 24 h and the cell survival rate was measured. Fig.15As shown, no obvious cytotoxicity was detected after DPA-CuNCs with a concentration range of 0.1 to 10 μg / mL were co-incubated with cells for 24 h. When the concentration reached 10 μg / mL, the cell survival rate was still close to 90%, indicating that DPA-CuNCs have good biocompatibility.
[0087] From the above examples, it can be seen that the DPA-CuNCs synthesized with penicillamine as a reducing agent and a stabilizing ligand have good dispersibility in water, high stability, strong catalytic activity, fluorescent properties and good biocompatibility, excellent performance, and a wide range of applications. At the same time, the stability of the catalytic activity and fluorescent properties of CuNCs is guaranteed.
[0088] Difficult separation, low yield and complex process are the limitations of CuNCs synthesis. Therefore, it is of great significance to design and develop new synthesis strategies to effectively improve the purity and yield of CuNCs. The synthesis process of this method adopts a one-pot method, uses a simple reflux condensation device, has a low reaction temperature, a short reaction time, and is purified by water washing and centrifugation. Therefore, the synthesis technology of DPA-CuNCs has the advantages of convenient operation, simple process, green environmental protection, high synthesis efficiency, and low development cost.
[0089] Although the specific embodiments of the present invention have been described in detail, it will be understood by those skilled in the art that various modifications and changes may be made to the details according to all the teachings that have been published, and these changes are within the scope of protection of the present invention. The entire invention is given by the attached claims and any equivalents thereof.
Claims
1. A use of copper nanoclusters in visual qualitative or quantitative analysis of cholesterol or glucose, characterized in that: The enzymatic kinetics of H2O2 K m The value is 3.99 mM, The copper nanoclusters are prepared by the following steps: 1) Weigh 0.2983-0.5966 g of penicillamine and add it to a 250 mL three-necked flask containing 50-100 mL of pH=3 acetic acid-acetate buffer solution. Dissolve it fully under magnetic stirring at 400-600 rpm. Then add 2.5-5.0 mL of 0.1-0.2 mol / L copper nitrate solution. The solution quickly turns into a yellow transparent solution. 2) Continue stirring until a small amount of white turbidity appears in the solution. Slowly heat the solution to 25-60 °C and react for 20-60 min to complete the reaction. 3) After the product is cooled, a light yellow emulsion is obtained. The light yellow precipitate is separated by centrifugation at 5000-10000 rpm for 5-10 min, and then washed with ultrapure water 2-3 times. The precipitate in the centrifuge tube is collected and freeze-dried in a freeze dryer. The freeze-dried powder sample is stored in a 4 ℃ refrigerator for subsequent use; The average particle size of the copper nanoclusters is 2.5-5.5 nm.
Citation Information
Patent Citations
Ratiometric fluorescent probe, and preparation method and application thereof
CN110591696A